Leg length difference in cyclists: kinetic imbalances and correctional options - Mann, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: The purpose of this study was to investigate the relationship of leg length differences and kinetic imbalances in addition to the effect of existing correctional procedures on such imbalances in cycling. Methodology: On a preliminary visit, total, upper and lower leg lengths were measured from the greater trochanter of the femur (GT) to heel (H), the GT to lateral condyle (LC), and LC to H, respectively. Two interventions: crank length (CL) and cleat wedge (CW) and a control (normal bike set-up (N)) were performed in a randomised order with a 2-5 d period between trials. Participants (n=10) performed a maximal isokinetic test (to allow for normalisation of EMG data followed by three 15min work sessions (CL: CW: N) at ventilatory threshold (VT). Heart rate, cadence, power output and expired air were averaged over each 15min interval. Net torque, EMG taken from left and right vastus lateralis (VL), were taken and averaged during 40-50s of the 5th, 10th and 15th min. Video footage synchronised with torque measurements was digitised and used to analyse 2D mechanical angles (thigh to horizontal, knee joint and ankle joint). Results: There were no significant differences (p>0.05) between conditions indicating reliability for power output (W), cadence (rpm), VO2 (L•min-1) and HR (bpm), averaged over each 15min period. In the cleat wedge condition, there was a reduction in between-leg variance (P<0.05) and a small effect size (ES = 0.18) between left and right leg torque. EMG variability reduced under the same condition giving a medium effect size (ES = 0.51). Discussion: results suggest that, given a longer intervention using the CW condition, imbalances could be reduced leading to improved performance and minimising friction, pressure and overuse injuries conditions common to endurance cyclists. Further research is required, using more subjects and an intervention period, as to how cyclists optimise force production while reducing variability between left and right legs.